Acidosis in models of cardiac ventricular myocytes - Crampin, E; Smith, N; Langham, A; Clayton, R; Orchard, C (2006)
The effects of acidosis on cardiac electrophysiology and excitation-contraction coupling have been studied extensively. Acidosis decreases the strength of contraction and leads to altered calcium transients as a net result of complex interactions between protons and a variety of intracellular processes. The relative contributions of each of the changes under acidosis are difficult to establish experimentally, however, and significant uncertainties remain about the key mechanisms of impaired cardiac function. In this paper, we review the experimental findings concerning the effects of acidosis on the action potential and calcium handling in the cardiac ventricular myocyte, and we present a modelling study that establishes the contribution of the different effects to altered Ca2+ transients during acidosis. These interactions are incorporated into a dynamical model of pH regulation in the myocyte to simulate respiratory acidosis in the heart.